2000
DOI: 10.2337/diacare.23.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes: is a higher cesarean section rate inevitable?

Abstract: 15 Gestational diabetes mellitus (GDM) is any degree of glucose intolerance with onset or first recognition during p regnancy (1). Women with undiagnosed or poorly managed GDM are at incre a s e d risk of having a large for gestational age (LGA) infant. A LGA infant may be re s p o nsible for cephalo-pelvic dispro p o rtion and hence an increased risk of obstetric intervention including cesarean section.While it is not invariable that women with GDM will have a higher section rate (2,3), it has been suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
1
24
0
2
Order By: Relevance
“…[23][24][25] However, in Australia, this in the past has not been inevitable. 26 Two major treatment interventions for women with GDM where the obstetric care provider was blinded to the glucose results showed no change 27 or a reduction 28 in the rate of sections. If in Australia overall, with an increase in the prevalence of HIP, the percentage of women having sections, with the subsequent neonatal interventions and increased length of hospital stay, were to remain unchanged or to increase, then much of the potential health and economic advantages would not be apparent.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] However, in Australia, this in the past has not been inevitable. 26 Two major treatment interventions for women with GDM where the obstetric care provider was blinded to the glucose results showed no change 27 or a reduction 28 in the rate of sections. If in Australia overall, with an increase in the prevalence of HIP, the percentage of women having sections, with the subsequent neonatal interventions and increased length of hospital stay, were to remain unchanged or to increase, then much of the potential health and economic advantages would not be apparent.…”
Section: Discussionmentioning
confidence: 99%
“…A New South Wales study reported a Caesarean section rate of 20% in women with GDM, compared to 16% in non-diabetic women, and the difference was partly explained by age and parity. 87 A Cochrane review also found that reduction in macrosomia is not necessarily followed by significant differences in the rates of sections, forceps deliveries or birth trauma. 65 Santini and Ales 88 have calculated that to prevent one case of macrosomia, 3716 women would have to be screened; 250 would require further tests such as ultrasound, and 134 more women would have Caesarean sections.…”
Section: The Benefit From the Screening Programmementioning
confidence: 99%
“…However, the increase in section rates as reported in Canada 9 was not seen in New South Wales. 14 The harms of intervention also need to be considered, including insulin treatment and hypoglycaemia. 7 Santini and Ales (1990) 15 calculated that to prevent one case of macrosomia, 3716 women would need to be screened, and 134 more women would have caesarean sections.…”
Section: (8) There Should Be An Effective Treatment or Intervention Fmentioning
confidence: 99%